PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG PENJUMLAHAN DAN PENGURANGAN BILANGAN PADA SISWA KELAS 1 SD MUHAMMADIYAH 2 PAREPARE - Rosnah Rosnah (Al-Ishlah: Jurnal Pendidikan Islam, 2015)
Research problems namely is the implementation of cooperative learning model Teams-Games-Tournaments can improve student learning outcomes on addition and reduction of numbers in the first grade of SD Muhammadiyah 2 Pare Pare? from the formulation of the problem, the research aims: to improve learning outcomes the sum of mathematics in the subject and reduction of numbers by applying cooperative learning Teams-Games-Tournaments. The approach used in this study is a qualitative approach. Classroom action research (PTK) was implemented in the first grade students of SD Muhammadiyah 2 Pare Pare totaling 17 people by focusing on two main aspects, namely: (1) aspect of the learning process; and (2) aspects of learning outcomes. The second aspect of the focus of which will be observed during the study with research procedures, ie: action planning, action, observation, and reflection. From the implementation of the measures obtained data collected by observation, achievement test and documentation. Furthermore, the data is analyzed and processed by descriptive quantitative and qualitative descriptive. Results of the study showed that: the teacher's activities in meyajikan materials with cooperative learning model Teams-Games-Tournaments tend to increase; activity of students in the learning process, also tend to be the better; and learning outcomes the first cycle and the second cycle are at sufficient qualification, and the third cycle is at a good qualifying.